2022
DOI: 10.3899/jrheum.220658
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Service Delivery and Access to Rheumatologists Before and During the COVID-19 Pandemic in a Canadian Universal Healthcare Setting

Abstract: Objective To describe changes in service delivery and access to rheumatologists pre- and during the COVID-19 pandemic periods. Methods We conducted a population-based study in Ontario, Canada. Patient visits with rheumatologists were ascertained using billing claims data. Contacts with rheumatologists were separately defined by the type of patient encounter (including office visits, telemedicine visits, and new patient consultations). Changes in the total weekly volume of encounters and monthly rates after COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In our study, patients initiating apremilast via telehealth were more likely to have seen a rheumatologist. This is consistent with a study that reported a sharp increase in telehealth use by rheumatologists [ 38 ], and a systematic review showed telehealth visits led to similar disease activity control and patient-reported outcomes as in-person care [ 51 ]. Finally, we found patients initiating apremilast via telehealth were more likely to have had a telehealth visit during baseline.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, patients initiating apremilast via telehealth were more likely to have seen a rheumatologist. This is consistent with a study that reported a sharp increase in telehealth use by rheumatologists [ 38 ], and a systematic review showed telehealth visits led to similar disease activity control and patient-reported outcomes as in-person care [ 51 ]. Finally, we found patients initiating apremilast via telehealth were more likely to have had a telehealth visit during baseline.…”
Section: Discussionsupporting
confidence: 91%
“…Telehealth services have expanded over the last 5 years, but the increase in these services significantly increased during the COVID-19 pandemic as in-person medical services for multiple diseases were postponed or cancelled [ 36 , 37 ]. In addition, patients receiving healthcare via telehealth services maintained or increased medication adherence and increased medication fills compared to those with in-person visits [ 28 , 38 44 ]. Our study findings corroborate those from previous studies using telehealth on patients with PsO and PsA [ 45 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This risk period after exposure is based on the concept that if individuals with RA experience a flare after a vaccine, delays in seeing their rheumatologist may be because of potential access issues heightened during the pandemic. 17 Analysis. Events were ascertained across control and risk periods.…”
Section: Study Populationmentioning
confidence: 99%
“…Hospital patient volumes decreased during the beginning stages of the pandemic in multiple medical disciplines, including radiology, emergency, and surgery departments [1][2][3][4]. Decreases in volumes were also seen in individual practices, such as those in dermatology and rheumatology [5,6]. The effects on patient volumes during the COVID-19 pandemic were also seen internationally, with hospitals around the world noting a decrease in hospital revenue [7,8].…”
Section: Introductionmentioning
confidence: 99%